Medical nutrition therapy in renal disease. A clinical dietetic-based case study - Awan, Rabbia Younas (Progress in Nutrition, 2019)
This paper explains the significance of medical nutrition therapy and its application in clinical dietetic practices with the help of nutrition care plan. It contains a case study of an indoor patient diagnosed with chronic kidney disease, diabetes mellitus and hypertension. A whole nutrition care process was formulated. The pre-interventional results of nutrition intervention plan were compared with the post-interventional results. A visible improvement in all categories of assessment was observed. The BMI was reduced with 0.1 kg/m2, blood haemoglobin and calcium levels were raised, and BUN, BGL, creatinine, sodium and potassium were reduced noticeably. The dietary consumption trends were also altered towards the recommended ones. Proceeding through all four steps of nutrition care process i.e. nutrition assessment, nutrition diagnosis, nutrition intervention and nutrition monitoring, a complete execution of medical nutrition therapy was observed.